Decoding the Enigma: Exploring Influential Factors in the Phenomenon of Online Shopping Cart Abandonment - T. S. Arthi (Journal of Informatics Education and Research, 2024)
This study examined the factors that contribute to online shopping cart abandonment in several product categories. The main goals were to examine how price, user experience, infrequent purchase behaviour, and cart abandonment interact when shopping online, with a focus on various product categories. An online survey method was used to collect responds from 302 respondents in Coimbatore and Chennai. Reliability test and Spearman's Correlation Coefficient was conducted using IBM SPSS version 16.0. Specific to product categories, the results showed a significant association between low purchase frequency, cost, user experience, and cart abandonment. Notably, the results highlight how price has the biggest impact on shopping cart abandonment, with user experience and infrequent purchases coming in second and third position. These findings greatly advance our understanding of customer behaviour in the context of online buying and have useful ramifications for companies and legislators looking to maximise tactics throughout different product categories.